Policy Responses to Aid Surges in Countries with Limited International Capital Mobility The Role of the Exchange Rate Regime - Berg, Andrew (International Monetary Fund, 2014)
We study the role of the exchange rate regime, reserve accumulation, and sterilization policies in the macroeconomics of aid surges. Absent sterilization, a peg allows for almost full aid absorption - an increase in the current account deficit net of aid-delivering the same effects as those of a flexible regime but with a necessary increase in inflation. Regardless of the regime, policies that limit absorption-and result in large accumulation of reserves-are welfare reducing: they help reduce the real appreciation (and inflation under the peg), but at the expense of reducing private consumption and investment, and therefore medium-term growth